Islamic Moderation as an Approach to Fiqh Learning at Pesantren - Muizzuddin, M.; Masyhudi, Habib; Sari, Nabila Septya (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This article examines the implementation of Islamic moderation in fiqh learning and identifies the impact of the implementation of Islamic moderation in fiqh learning at Pesantren Mambaus Sholihin in Gresik. This research employs a qualitative-phenomenological approach, utilizing interviews, observations, and documentation for data collection. The gathered data undergoes analysis through reduction, presentation, and conclusion drawing. This methodology enables an in-depth understanding of participants' experiences and perspectives. The results showed that he implementation of Islamic moderation in fiqh learning at Pesantren Mambaus Sholihin successfully merges salafiyah traditions with modern challenges. Its curriculum integrates classical fiqh with contemporary issues like online transactions and maqashid sharia, emphasizing tolerance for different madhhabs, flexibility during emergencies, and gender equality. Teaching methods like bandongan, sorogan, discussions, and real case studies ensure students not only grasp theory but can also apply it in daily life. This holistic approach aims to produce a generation that is noble, broad-minded, and capable of facing modern challenges without abandoning Islamic traditions. This application has a positive impact, fostering a harmonious, inclusive pesantren environment free from extremism. Students are taught to think critically, fairly, and tolerantly towards differences. However, challenges persist, including internal differences in views, external extremist ideologies, and limited teacher resources and abilities. Despite these obstacles, Islamic moderation proves relevant as an adaptive learning model for forming a contextual and inclusive understanding of fiqh.  This study promotes Islamic moderation education to prevent extremism and encourage contextual understanding.